Intermarriage and the Intergenerational Transmission of Ethnic Identity and Human Capital for Mexican Americans - Brian Duncan; Stephen Trejo (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2009)
Using microdata from the 2000 U.S. Census and from recent years of the Current Population Survey (CPS), we investigate whether selective intermarriage and endogenous ethnic identification interact to hide some of the intergenerational progress achieved by the Mexican-origin population in the United States. First, using Census data for U.S.-born youth ages 16-17 who have at least one Mexican parent, we estimate how the Mexican identification, high school dropout rates, and English proficiency of these youth depend on whether they are the product of endogamous or exogamous marriages. Second, we analyze the extent and selectivity of ethnic attrition among second-generation Mexican-American adults and among U.S.-born Mexican-American youth. Using CPS data, we directly assess the influence of endogenous ethnicity by comparing an "objective" indicator of Mexican descent (based on the countries of birth of the respondent and his parents and grandparents) with the standard "subjective" measure of Mexican self-identification (based on the respondent's answer to the Hispanic origin question). For third-generation Mexican- American youth, we show that ethnic attrition is substantial and could produce significant downward bias in standard measures of attainment which rely on ethnic self-identification rather than objective indicators of Mexican ancestry.
Keywords: 330